(untitled) (Eurasian Journal of Research, Development and Innovation, 2026)
The issue of international financing is one of the central issues in contemporary economic and development literature, especially in light of the rapid changes the world is witnessing in terms of international economic relations and the increasing need to mobilise financial resources to achieve sustainable development. The United Nations launched the 2030 Agenda for Sustainable Development, which set 17 global goals that require the mobilization of huge financial resources that developing countries, including Iraq, cannot achieve without innovative and effective external support. Analyzing the international financing instruments used in Iraq since 2015 and assessing their contribution to achieving the Sustainable Development Goals is doubly important in light of the structural challenges facing the Iraqi economy, the most significant of which are heavy dependence on oil, weak institutions, and rising levels of poverty and unemployment, as well as the urgent need to rebuild infrastructure and strengthen governance and transparency. Studying the practical aspects of international financing in Iraq helps to develop more effective policies for achieving sustainable development in all its aspects .